Knowledge Spillovers, ICT and Productivity Growth - Carol Corrado; Jonathan Haskel; Cecilia Jona-Lasinio (Institute for the Study of Labor (IZA), 2014)
This paper looks at the channels through which intangible assets affect productivity. The econometric analysis exploits a new dataset on intangible investment (INTAN-Invest) in conjunction with EUKLEMS productivity estimates for 10 EU member states from 1998 to 2007. We find that (a) the marginal impact of ICT capital is higher when it is complemented with intangible capital, and (b) non-R&D intangible capital has a higher estimated output elasticity than its conventionally-calculated factor share. These findings suggest investments in knowledge-based capital, i.e., intangible capital, produce productivity growth spillovers via mechanisms beyond those previously established for R&D.
Keywords: O47; E22; E01; 330; productivity growth; economic growth; intangible capital; intangible assets; ICT; spillovers